Degradasi Moral dan Etika Bermedia Sosial dalam Film ‘Budi Pekerti’ - Fitriani, Annisa; Poedjadi, Maudy Rizkiana; Recky (LITERAKOM: Jurnal Literasi dan Komunikasi, 2024)
Film is an artistic expression that not only functions as entertainment, but also as a means of conveying moral messages and character building. This film, which was released on November 2 2023, carries a deep message. This film is the film "Budi Pekerti" by Wregas Bhanuteja. "Budi Pekerti" not only presents an emotionally moving story, but also considers the impact of technology on character formation. Through the main character who faces various obstacles in life in this world, this film conveys the message of the importance of ethics in interacting on social media and provides an overview of the phenomenon of moral degradation due to irresponsible behavior on social media. The aim of this research is to identify the representation of the moral message contained in the film "Budi Pekerti." The method used is a qualitative descriptive method with John Fiske's semiotic framework, utilizing a constructivist paradigm. The subject of this research is the film "Budi Pekerti". The research results show forms of moral messages in films such as politeness, technological wisdom, and responsibility.